Secondary metabolites from Spiranthes sinensis (Orchidaceae). (October 2019) - Yan, Yang; Wu, Chuanhai; Zhou, Hui; Feng, Xiaoye; Li, Yan-Fang
Abstract: One new flavonol glycoside (1 ) and nine known compounds (2 –10 ) were obtained from the n -BuOH soluble fraction of the whole plants of Spiranthes sinensis . The structure of compound1 was elucidated based on the combination of spectroscopic ( 1 H-NMR, 13 C-NMR, HSQC, and HMBC as well as HR-ESI-MS) and chemical methods. The occurrences of eight compounds (2-9 ) in this genus were firstly reported while five of them (2–6 ) were obtained from Orchidaceae for the first time. Furthermore, the chemotaxonomic significance of these compounds was discussed. Highlights: One new flavonol glycoside and nine known compounds were obtained from Spiranthes sinensis. Eight compounds had never been found previously in this genus. Five compounds were isolated from the family Orchidaceae for the first time. These compounds provide evidence for chemotaxonomic studies of S. sinensis and the genus Spiranthes.